A novel FBN2 mutation cosegregates with congenital contractural arachnodactyly in a five‐generation Chinese family. Issue 8 (3rd July 2018) - Zhou, Shiyuan; Wang, Fengyu; Dou, Yongheng; Zhou, Jiping; Hao, Gefang; Xu, Chengqi; Wang, Qing K.; Wang, Haili; Wang, Pengyun
Key Clinical Message: We identified a novel heterozygous mutation (c.4177T>G and p.Cys1393Gly) in FBN2 that cosegregated with congenital contractural arachnodactyly (CCA) in a five‐generation Chinese family. This mutation may cause the loss of the disulfide bond between Cys 1393 and Cys 1378 residues of fibrillin‐2. Our study expands the genetic profile of CCA. Abstract : We identified a novel heterozygous mutation (c.4177T>G and p.Cys1393Gly) in FBN2 that cosegregated with congenital contractural arachnodactyly (CCA) in a five‐generation Chinese family. This mutation may cause the loss of the disulfide bond between Cys 1393 and Cys 1378 residues of fibrillin‐2. Our study expands the genetic profile of CCA.